Evolving landscape of clinical trials in gastroenteropancreatic neuroendocrine neoplasms in the past two decades - Kaili Yang; Jiarui Li; Yuejuan Cheng; Chunmei Bai (Endocrine Connections, 2023)
Background: Gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) are heterogenous malignancies that require well-designed trials to develop effective management strategies. This cross-sectional study aimed to illustrate the current landscape of clinical trials in GEP-NENs to provide insights for future research. Materials and methods: We reviewed all clinical trials registered on ClinicalTrials.gov between 1 January 2000 and 31 December 2021 with GEP-NEN in the ‘condition or disease’ field. Results: We included 206 eligible trials. Most trials enrolled less than 50 patients (59.8%) and were sponsored by institutions other than government or industry (67.0%). Most trials were conducted in high-income countries (86.6%) and countries located in Europe (30.1%) or Northern America (29.6%). The overall result reporting rates of GEP-NEN trials was 41.4%, and the median time from primary completion to result reporting was 101 months. Characteristics that improved the reporting of results included larger sample size, tumor differentiation specification for inclusion, p rogression-free survival as primary endpoint, industry sponsorship, and multicenter or multinational participation (all P < 0.05). Compared with trials registered between 2000 and 2011 (n = 28), trials registered between 2012 and 2021 (n = 178) were more likely to specify the Ki-67 index for inclusion (68.0% vs 35.7%, P = 0.002) and to be conducted outside Europe or Northern America (16.4% vs 3.7%, P = 0.02), while the sample size and the sponsorship did not change significantly. Conclusions: Novel management options have been explored for GEP-NENs with more specific inclusion criteria during the past two decades. More eff orts are needed to promote international collaborations in clinical trials and enhance timely result dissemination.